Hubungan Pola Asuh Ibu dengan Status Gizi Balita - Dayatin, Ima; ., Tini; Sinaga, Elisa Goretti (JIDAN Jurnal Ilmiah Bidan, 2023)
Background: Nutritional problems occur in every life cycle. The first five years of life are a critical period because during this period very rapid growth and development occur. A mother's parenting style determines the nutritional status of toddlers. Objective: To determine the relationship between maternal parenting patterns and the nutritional status of toddlers at Posyandu Mawar, Bunga Jadi Village, Muara Kaman District.Method: This research uses Cross Sectional. The sample for this research was all 30 toddlers aged 36-60 months at Posyandu Mawar, Bunga Jadi Village, Muara Kaman District, using the technique of Total Sampling. The research instrument was a questionnaire on parenting patterns and KMS for toddlers. Statistical test using Test Somers’D. Results: Test results Somers’D obtained a significance value of 0.942 > 0.05 (ρvalue> α), meaning that there is no relationship between maternal parenting patterns and the nutritional status of toddlers at Posyandu Mawar, Bunga Jadi Village, Muara Kaman District, as a recommendation for Health workers should always carry out health promotions related to toddler nutrition and monitoring growth and development among the community.